One-by-One Comparison of Lymph Nodes Between (18)F-FDG Uptake and Pathological Diagnosis in Esophageal Cancer - Yoshimura, Shuntaro (Clin Nucl Med, 2020)
Esophagectomy with extended lymph node (LN) dissection is a standard treatment for resectable esophageal cancer to prevent recurrence, but severe, potentially life-threatening postoperative complications are still important issues. Accurate diagnosis of LN metastases would enable the decision to dissect or leave the LNs in regions with high risk of complications. Advancements in intraoperative gamma probe and radioactivity detectors have made intraoperative navigation surgery possible using a radiotracer as a marker. (18)F-FDG is one such candidate markers, and the diagnostic power of FDG through counting the radioactivity close to each LN should be elucidated. MATERIALS AND METHODS: In 20 patients, 1073 LNs including 38 metastatic LNs were prospectively investigated. Preoperative FDG PET was performed on the same day before esophagectomy and visually surveyed in each LN station to identify abnormal uptake. The FDG radioactivity of each individual dissected LN was measured by a well-type counter, and the pathological diagnosis was compared with LN radioactivity on a one-by-one basis and with the preoperative FDG PET findings for each LN station. RESULTS: Lymph node station-based analysis showed a sensitivity and specificity of 28.6% and 96.7%, respectively. One-by-one LN-based analysis using a cutoff value obtained from the receiver operating characteristic curve showed a sensitivity and specificity of 94.7% and 78.7%, respectively, demonstrating higher accuracy compared with the use of LN weight or the shortest diameter. CONCLUSIONS: The FDG uptake by each LN is a potentially useful marker for navigation surgery in esophageal cancer and has higher accuracy than LN weight or diameter.